Determinants of dietary and physical activity behaviours among women of reproductive age in urban Uganda, a qualitative study. Issue 12 (1st August 2021) - Yiga, Peter; Ogwok, Patrick; Achieng, Julian; Auma, Mary Devota; Seghers, Jan; Matthys, Christophe
Abstract: Objective: To explore determinants of dietary and physical activity behaviours among women of reproductive age. Design: Data were collected through focus group discussions (FGD). The FGD guide was based on a modified theoretical framework; theory of planned behaviour was incorporated with constructs of health belief model, precaution adoption process model, social cognitive and social support theory. Discussions were audio recorded, transcribed verbatim and analysed thematically. Setting: Kampala, Uganda. Participants: Women were categorised into young adults; 18–34 years and adults; 35–45 years Results: Separate FGD with independent participants were conducted for dietary and physical activity behaviours until data saturation was achieved. Six FGD were conducted per behaviour. Determinants of dietary behaviours at intra-individual level included gaps in food skills, knowledge and self-efficacy, food safety concerns, convenience, finances and physiological satisfaction. The social-cultural norms were relationship between vegetable consumption and low social status, consideration of fruits as a snack for children and not food and habitual orientation towards carbohydrate foods. At environment level, social networks and increased availability of energy-dense, nutrient poor, street and processed foods influence dietary behaviour. For physical activity, intra-individual determinants were knowledge gaps and self-efficacy, while socio-cultural norms included gender stereotypes. Home (limited space and sedentary entertainment like social media and TV) and physical environment (cheap motorised transportation) influence physical activity. Conclusion: The existing cultural beliefs promote dietary and physical activity behaviours which are divergent from healthy recommendations. Therefore, a comprehensive intervention is needed to address socio-cultural misconceptions, financial and time limitations in urban Uganda.